Delta-type solutions for a system of induction equations with discontinuous velocity field - Shafarevich, A. I.; Esina, A. I. (Methods of Functional Analysis and Topology, 2014)
We study asymptotic solutions of a Cauchy problem for induction equations describing magnetic field in a well conducting fluid. We assume that the coefficient (the velocity field of the fluid) changes rapidly in a small vicinity of a two-dimensional surface. We prove that the weak limit of the solution has delta-type singularity on this surface; in the case of a perfectly conducting fluid, we describe several regularizations of the problem with discontinuous coefficients which allow to define generalized solutions.